2019
DOI: 10.1155/2019/2758501
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Microbial Diversity of Coastal Sand Dunes: Need for Exploration in Odisha Coast of India

Abstract: Coastal sand dunes are hips and strips formed by sand particles which are eroded and ground rock, derived from terrestrial and oceanic sources. This is considered as a specialized ecosystem characterized by conditions which are hostile for life forms like high salt, low moisture, and low organic matter content. However, dunes are also inhabited by diverse groups of flora, fauna, and microorganisms specifically adapted to these situations. Microbial groups like fungi, bacteria, and actinobacteria are quite abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…The justification presented above may be applicable to the present work, since dune soil, characteristically known for low organic matter decomposition and low soil fertility (Camprubíet et al, 2010;Oliveira and Landim, 2020), the same characteristics were presented by the substrate used, and as suggested by Smith and Read (2008) and Nayak et al (2019), the AMF were probably stimulated in soils with low fertility. The percentage of root colonization (% M) by AMF increased from 6.4 to 10.2% throughout the experiment (Figure 4).…”
Section: Resultssupporting
confidence: 61%
“…The justification presented above may be applicable to the present work, since dune soil, characteristically known for low organic matter decomposition and low soil fertility (Camprubíet et al, 2010;Oliveira and Landim, 2020), the same characteristics were presented by the substrate used, and as suggested by Smith and Read (2008) and Nayak et al (2019), the AMF were probably stimulated in soils with low fertility. The percentage of root colonization (% M) by AMF increased from 6.4 to 10.2% throughout the experiment (Figure 4).…”
Section: Resultssupporting
confidence: 61%
“…These organic compounds can generate growth, production, and high number of bacteria in these zones of marine beach. Moreover, dune which acts as a biocatalytic filter is enriched with humic substances originating from decaying roots of grasses growing on it [66,67]. Humic substances may be utilized by bacteria very intensively in metabolic processes as a good source of carbon or energy [68].…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended to use non-pathogenic microbial strains for industrial processes (Bennur et al, 2015). Nayak et al (2019) reported extremophiles isolated from plantations prevalent in the dune ecosystem for extracellular production of chitinases. There is much scope for getting diverse endophytes from extreme environments.…”
Section: Chitinasesmentioning
confidence: 99%